RF-induced heating effects of metallic biomaterial designs at 1.5T MRI exposure. (8th May 2023) - Akdogan, Gulsen; Istanbullu, O. Burak
This study analyses the performance of implantable bio-metals in magnetic resonance imaging (MRI) conditions to ensure that patients with MRI-conditional implants are not precluded from MRI applications. 316L, 316LVM, Ti-alloy, and CoCrMo-alloy specimens in different geometries were placed in a phantom that imitates the thermal/electrical features of human anatomy. The phantom was scanned in a 1.5T-MRI using 'axial-T1 -gradient-echo', 'sagittal-T1 -gradient-echo', 'axial-T2 -spin-echo' and 'sagittal-T2 -spin-echo' imaging sequences. The specimens were examined regarding radiofrequency (RF) induced heating using a 2-channel-fiber-optical-temperature-transmitter and magnetic deflection/torque formation. 316LVM specimens that are not allowed to be in the MRI environment were found to be acceptable in the 1.5T-MRI environment since there was no magnetic deflection and RF-induced overheating. Ti-alloy specimens were found harmless under the same conditions. 316L and CoCrMo-alloy specimens were considered hazardous due to the magnetic deflection formation. This study demonstrates that bio-metals which were not allowed to be in MRI devices such as 316LVM are not harmful to patients in 1.5T MRI.